Ethical dimensions in robot creation industry - Shuriye, Abdi Omar (Serials Publications, 2005)
Engineering sciences are moving at a pace in which, as it seems, within few decades the advent of highly advanced and interactive technologies of semi human qualities may perhaps be brought into life form to revolutionize the manifold of human vivacity. Machines are now being taught to be self-controlling and self-initiating. Being one of the salient fields, it has for long intrigued engineers as to how to invent the adjacent human-like machine that could emulate human emotions, styles and patterns in precisely identical mode. The paper intends to religiously explore human creation in contrast with robotic formation